2015
DOI: 10.3109/21681805.2015.1059880
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of adoptive immunotherapy with sentinel node-derived T cells in muscle-invasive urinary bladder cancer

Abstract: Infusion of expanded autologous tumor-specific T lymphocytes is feasible and safe, and objective responses according to RECIST were recorded. One objective responder to immunotherapy displayed notably long overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…Indeed, CD4 + T cells have been demonstrated to promote tumor eradication through this feature, mediated partly by their ability to secrete IL-2 (142). Consistently, there are successful examples of the clinical use of CD4 + Teff cells in cancer immunotherapies, including ACT, as we have previously reported for in UBC (143) and others for melanoma (144). Taken together, CD4 + Teff cells, particularly the Th1 subset, reinforce multiple distinct aspects of the anti-tumor immune response, suggesting an underestimated potential of this cell compartment for the use in cancer immunotherapies.…”
Section: Anti-cancer Responses By Effector Cd8 + and Cd4 + T Cellssupporting
confidence: 66%
See 1 more Smart Citation
“…Indeed, CD4 + T cells have been demonstrated to promote tumor eradication through this feature, mediated partly by their ability to secrete IL-2 (142). Consistently, there are successful examples of the clinical use of CD4 + Teff cells in cancer immunotherapies, including ACT, as we have previously reported for in UBC (143) and others for melanoma (144). Taken together, CD4 + Teff cells, particularly the Th1 subset, reinforce multiple distinct aspects of the anti-tumor immune response, suggesting an underestimated potential of this cell compartment for the use in cancer immunotherapies.…”
Section: Anti-cancer Responses By Effector Cd8 + and Cd4 + T Cellssupporting
confidence: 66%
“…As discussed previously, immune responses are in general initiated in the lymph node. This notion combined with the hypothesis that immunosuppression would be less pronounced in the tumordraining lymph node, is the foundation for our groups' focus on this anatomical location, because it represents an alternative source for ACT (143). However, because tumors may induce neolymphangiogenesis, the lymphatic drainage system is frequently deranged which complicates the identification of this node(s).…”
Section: The Sentinel Node a Key Component Of The Tumor Microenvironmentioning
confidence: 99%
“…In this approach, lymphocytes are harvested and expanded, then re-infused into the patient. In UBC, a pilot study of infusion of T cells that were expanded ex-vivo from tumor draining lymph nodes reported 2 out of 6 patients with responses [34]. This process may be enhanced through genetic engineering of T cells to express chimeric antigen receptors (CARs).…”
Section: Therapeutic Targeting Of Dysfunctional Anti-tumor Immunitymentioning
confidence: 99%
“…67 ACT is still in the fairly early stages of testing in bladder cancer, with several ongoing trials, and a new study out of Sweden has just reported a couple highly promising results from a small cohort of individuals with metastatic UCC, including one patient who demonstrated a complete response. 68 More research into optimizing and expanding this technology is needed to assess its potential in UCC patients, and though it is a relatively high cost technology, due to the highly personalized nature of taking each individual patient’s own T-cells for the ex vivo modifications, that is also a large part of what makes it so appealing, at least in concept, in our current world of modern precision medicine.…”
Section: Immunotherapy: Promising New Horizonsmentioning
confidence: 99%